2020
DOI: 10.15252/emmm.202012088
|View full text |Cite
|
Sign up to set email alerts
|

BAM15‐mediated mitochondrial uncoupling protects against obesity and improves glycemic control

Abstract: Obesity is a leading cause of preventable death worldwide. Despite this, current strategies for the treatment of obesity remain ineffective at achieving long‐term weight control. This is due, in part, to difficulties in identifying tolerable and efficacious small molecules or biologics capable of regulating systemic nutrient homeostasis. Here, we demonstrate that BAM15, a mitochondrially targeted small molecule protonophore, stimulates energy expenditure and glucose and lipid metabolism to protect against diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 63 publications
12
77
0
Order By: Relevance
“…Indeed, hyperinsulinemic-euglycemic clamp studies demonstrated that BAM15 enhanced insulin sensitivity in skeletal muscle and white adipose tissue [ 111 ]. In support of this, oral dosing of BAM15 (∼85 mg/kg/day) was independently shown to prevent diet-induced obesity and improve glycemic control through alterations in whole-body energy expenditure, reduced adiposity, and AMPK-mediated suppression of WAT lipogenesis [ 112 ], supporting a crucial role of adipose tissue in mediating BAM15's beneficial effects. Interestingly, previous studies did not demonstrate an adipose-targeted depot for BAM15-mediated uncoupling [ 111 ]; however, differences in dose routes and pharmacokinetic study designs could explain these discrepancies.…”
Section: Therapeutic Relevance Of Mitochondrial Uncouplersmentioning
confidence: 99%
“…Indeed, hyperinsulinemic-euglycemic clamp studies demonstrated that BAM15 enhanced insulin sensitivity in skeletal muscle and white adipose tissue [ 111 ]. In support of this, oral dosing of BAM15 (∼85 mg/kg/day) was independently shown to prevent diet-induced obesity and improve glycemic control through alterations in whole-body energy expenditure, reduced adiposity, and AMPK-mediated suppression of WAT lipogenesis [ 112 ], supporting a crucial role of adipose tissue in mediating BAM15's beneficial effects. Interestingly, previous studies did not demonstrate an adipose-targeted depot for BAM15-mediated uncoupling [ 111 ]; however, differences in dose routes and pharmacokinetic study designs could explain these discrepancies.…”
Section: Therapeutic Relevance Of Mitochondrial Uncouplersmentioning
confidence: 99%
“…Oxidative phosphorylation (OXPHOS) and electron transfer (ET) capacity of permeabilized flight muscle was determined by high-resolution respirometry (Oroboros O2k; Innsbruck, Austria) as described previously (Simard et al 2018;Axelrod et al 2020). Briefly, 2-3 flies aged 3-7 or 30-35 days were sedated by cold exposure at 4°C for 7-10 min.…”
Section: Mitochondrial Respiratory Capacitymentioning
confidence: 99%
“…The use of regulators of oxidative stress in the comprehensive treatment of diabetes was found to maintain the structural and functional integrity of mitochondria. It has been shown that the mitochondrial-targeted antioxidants MitoTEMPO, MitoQ, BAM15, C12TPP, and CoQ10 partially prevent the ROS-induced disorders in oxidative phosphorylation and ultrastructure of mitochondria in animal models of obesity and insulin resistance [ 38 , 139 , 140 , 141 , 142 ]. Currently, the positive effects of CoQ10 and resveratrol as antidiabetic drugs have been demonstrated in most clinical trials [ 143 ].…”
Section: Mechanisms Of the Diabetes-induced Mitochondrial Dysfunctmentioning
confidence: 99%